Nylon elastomer composition as well as preparation method and application thereof

Through the use of compositions of nylon elastomers and polyolefin elastomers and amphiphilic branched copolymers, the problems of high market price and poor compatibility of nylon elastomers are solved, and high melt strength and good compatibility are achieved. Nylon elastomer compositions suitable for high-end applications such as sole foaming materials and large diameter pipes.

CN119286245AActive Publication Date: 2025-01-10WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411483553.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-10
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Nylon elastomers have high market prices and poor compatibility, which makes them difficult to meet the requirements of high melt strength, such as sole foaming materials with high foaming ratios and high-end large-diameter pipes.

Method used

The phase is prepared by using a composition of nylon elastomer, polyolefin elastomer, amphiphilic branched copolymer, antioxidant and lubricant, and by high-speed mixing, melt extrusion, water cooling, pelletizing and drying. A nylon elastomer composition with good capacity and an amphiphilic branched copolymer improves the interfacial strength and dispersion of nylon and polyolefins.

Benefits of technology

It improves the compatibility and melt strength of nylon elastomers and polyolefin elastomers, and is suitable for applications with high melt strength requirements, such as sole foaming materials and large-diameter pipes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098119690000101
    Figure BDA0005098119690000101
Patent Text Reader

Abstract

The invention discloses a nylon elastomer composition as well as a preparation method and application thereof. The composition comprises the following components: 100 parts of nylon elastomer; 20 to 100 parts of a polyolefin elastomer; 1 to 10 parts of an amphiphilic branched copolymer; 0.1 to 0.5 part of an antioxidant and 0.1 to 0.5 part of a lubricant. The composition disclosed by the invention is good in overall compatibility and high in elongation at break and melt strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nylon elastomer composition, in particular to a nylon elastomer composition and a preparation method and application thereof. Background Art

[0002] Nylon elastomer is the common name for thermoplastic polyamide elastomer, which refers to a type of block copolymer composed of high-melting-point crystalline polyamide (nylon) hard segments and non-crystalline polyether or polyester soft segments. This material has excellent softness, elastomer recovery rate and fatigue resistance, and is widely used in the manufacture of functional parts for mechanical and electrical precision instruments, automotive parts, sporting goods, etc. It can also be used to make high-end running shoe soles, compressed air pipes, fire hoses, etc. after foaming.

[0003] However, the market price of nylon elastomer is relatively high (about 100 yuan / kg), which is not conducive to product promotion. The main idea of ​​reducing product production costs is to use polyolefin elastomers with lower prices (less than 20,000 yuan / ton) to blend and modify nylon elastomers. However, due to the large difference in polarity between them and the poor compatibility between the two, how to improve the compatibility of the blended materials is the main direction of current research. On the other hand, there are few brands of nylon elastomer products on the market, and the performance is single, which cannot meet some nylon elastomer application fields with high melt strength requirements, such as sole foaming materials with high foaming ratios, high-end large-diameter pipes, etc. Summary of the invention

[0004] The present invention aims to provide a nylon elastomer composition with good compatibility and high melt strength, and a preparation method and application thereof.

[0005] In order to solve the above technical problems, the present invention first proposes a nylon elastomer composition.

[0006] A nylon elastomer composition comprises the following components in parts by weight: 100 parts of nylon elastomer; 20-100 parts of polyolefin elastomer; 1-10 parts of amphiphilic branched copolymer; 0.1-0.5 parts of antioxidant and 0.1-0.5 parts of lubricant;

[0007] The amphiphilic branched copolymer is a copolymer with a polyolefin elastomer as a linear main chain and a polyether polyol oligomer as a branched side chain.

[0008] As some specific examples of the nylon elastomer composition in the present invention, the nylon elastomer has a melt index of 4-40 g / 10 min under the test conditions of 235° C. and 2.16 kg;

[0009] As some specific examples of the nylon elastomer composition in the present invention, the polyolefin elastomer has a melt index of 0.5-5 g / 10 min under the test conditions of 235° C. and 2.16 kg;

[0010] Preferably, the polyolefin elastomer is selected from one or more of POE (polyolefin elastomer), POP (polyolefin plastomer), SBS (styrene-butadiene-styrene block copolymer), SEBS (hydrogenated SBS).

[0011] As some specific examples of the nylon elastomer composition of the present invention, the antioxidant is selected from a combination of one or more of antioxidant 1010, antioxidant 1098, antioxidant 168, and antioxidant H10;

[0012] Preferably, the lubricant is selected from one or more of ethylene bisstearamide, oleamide, silicone oil and paraffin.

[0013] The present invention also proposes a method for preparing the nylon elastomer composition as described above, comprising the following steps: mixing nylon 12 elastomer, polyolefin elastomer, amphiphilic branched polymer, lubricant and antioxidant at high speed for 10-20 minutes, melt extruding, water cooling, pelletizing and drying to obtain the nylon elastomer composition.

[0014] As some specific examples of the preparation method of the nylon elastomer composition in the present invention, the preparation method of the amphiphilic branched polymer is as follows:

[0015] S1, mixing a polyolefin elastomer, maleic anhydride and an initiator and then extruding the mixture to obtain a maleic anhydride grafted modified polyolefin elastomer;

[0016] S2, after mixing the polyether polyol, the monoacid and the catalyst, heating to 200-240°C, then evacuating to an absolute pressure of 100-500Pa, reacting for 0.5-1h; after stopping the evacuation, nitrogen is added to 100-300kPa, stirring is stopped and the temperature is lowered to obtain a monohydroxyl-terminated polyether polyol oligomer;

[0017] S3, after the maleic anhydride grafted modified polyolefin elastomer obtained in step S1 and the monohydroxyl-terminated polyether polyol oligomer are mixed, the temperature is raised to 200-240°C, evacuated to an absolute pressure of 100-500Pa, and the reaction is continued for 0.5-1h to obtain an amphiphilic branched polymer. The obtained amphiphilic branched copolymer is a copolymer with a polyolefin elastomer as a linear main chain and a polyether polyol oligomer as a branched side chain. The amphiphilic branched copolymer can improve the interfacial strength of nylon elastomer and polyolefin elastomer, realize a smaller phase size dispersion of polyolefin elastomer in nylon elastomer, avoid stress cracking at the interface of the two phases during use, and improve the elongation at break of the material. In addition, the special dendritic structure is easy to form a network structure in the nylon elastomer and polyolefin elastomer blending system, further improving the melt strength of the blending system.

[0018] As some specific examples of the method for preparing the nylon elastomer composition of the present invention, in step S1, the amount of maleic anhydride added is 2-10% of the mass of the polyolefin elastomer;

[0019] Preferably, the initiator is selected from at least one of benzoyl peroxide, azobisisobutyronitrile and dicumyl peroxide, and more preferably, the amount of the initiator added is 0.2-0.5% of the mass of the polyolefin elastomer;

[0020] Preferably, the extrusion temperature in step S1 is 150-250°C.

[0021] As some specific examples of the method for preparing the nylon elastomer composition of the present invention, in step S2, the number average molecular weight of the polyether polyol is 500-3000;

[0022] Preferably, the monoacid is one or more of formic acid, acetic acid, propionic acid, and n-butyric acid. More preferably, the amount of the monoacid added is (0.95-1.05):1 based on the molar ratio of carboxyl group to terminal hydroxyl group of the polyether polyol.

[0023] Preferably, the catalyst is selected from one or more of tetrabutyl titanate, antimony glycol, dioctyltin oxide, zirconium n-propoxide, and more preferably, the added amount of the catalyst is 0.05-0.2% of the mass of the polyether polyol.

[0024] As some specific examples of the method for preparing the nylon elastomer composition of the present invention, in step S3, the mass ratio of the monohydroxyl-terminated polyether polyol oligomer to the maleic anhydride graft-modified polyolefin elastomer is 1:(2-10);

[0025] The present invention also provides an application of the nylon elastomer composition as described above or the nylon elastomer composition prepared by the method described above in a shoe sole foaming material and a large-diameter pipe.

[0026] The present invention improves the compatibility of nylon elastomer and polyolefin elastomer by using amphiphilic branched copolymer, and realizes submicron-sized dispersion of polyolefin elastomer in nylon elastomer. At the same time, the presence of amphiphilic branched copolymer can effectively improve the melt strength of the blending system of nylon elastomer and polyolefin elastomer, and is particularly suitable for application occasions requiring high melt strength, such as supercritical CO2 foaming, pipe extrusion and other application fields. DETAILED DESCRIPTION

[0027] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0028] The main test methods involved in the following embodiments of the present invention are as follows:

[0029] (1) Determination of the size of the dispersed phase of polyolefin elastomer: The nylon elastomer / polyolefin elastomer blend strip was fractured in liquid nitrogen, and the fracture surface was etched with n-heptane at 60°C for 3 min. The fracture surface was then gold-sprayed and observed using a scanning electron microscope (JSG-5900LV, Japan).

[0030] (2) Melt strength test: A Gottfert RHEOTENS71.97 melt strength tester was used at a test temperature of 180°C.

[0031] (3) Elongation at break: tested in accordance with ISO 527 standard.

[0032] Unless otherwise specified, the raw materials and reagents involved in the following examples of the present invention can be purchased through commercial channels.

[0033]

Preparation Example 1

[0034] (1) 5 kg POE (Dow Engage 8150, MFR = 1.0 g / 10 min) and 100 g maleic anhydride monomer (Beijing Inokai Technology Co., Ltd.) and 10 g benzoyl peroxide initiator (Beijing Inokai Technology Co., Ltd.) were uniformly mixed using a high-speed mixer; extrusion was performed using a twin-screw extruder with an aspect ratio of 68, and the temperatures from the feed section to the die were set to 160° C., 210° C., 220° C., 220° C., 210° C., and 200° C. in sequence, and the screw speed was 100 rpm. The extruded material was pulled, water-cooled, pelletized, and dried to obtain a maleic anhydride grafted modified polyolefin elastomer (TPE-MA-1).

[0035] (2) 1800 g of polyethylene glycol (Mn=600, Beijing Inokai Technology Co., Ltd.), 138 g of formic acid (Beijing Inokai Technology Co., Ltd.), and 3.6 g of ethylene glycol antimony were added to a 10 L reactor, replaced with nitrogen three times, heated to 240° C., and then evacuated to an absolute pressure of 100 Pa for 60 min to complete the esterification reaction; the evacuation was stopped, nitrogen was added to 100 kPa, stirring was stopped and the temperature was lowered to 30° C. to obtain a monohydroxy-terminated polyether polyol oligomer CJW-001.

[0036] (3) 16 kg of TPE-MA-1 was added to a reactor containing 1938 g of monohydroxy-terminated polyether polyol oligomer CJW-001. After nitrogen replacement three times, the temperature was raised to 240° C. and the absolute pressure of the reaction system was reduced to below 100 Pa by vacuum. The reaction was continued for 60 min. The reaction was then pulled, water-cooled, and pelletized to obtain amphiphilic branched copolymer pellets (TPE-PA-1).

[0037]

Preparation Example 2

[0038] (1) 5 kg of SEBS (Baling Petrochemical YH-533, MFR = 5.0 g / 10 min) and 250 g of maleic anhydride monomer (Beijing Inokai Technology Co., Ltd.) and 15 g of azobisisobutyronitrile (Beijing Inokai Technology Co., Ltd.) initiator were uniformly mixed using a high-speed mixer; extrusion was performed using a twin-screw extruder with an aspect ratio of 68, and the temperatures from the feed section to the die were set to 160° C., 210° C., 220° C., 220° C., 210° C., and 200° C. in sequence, and the screw speed was 100 rpm. The extruded material was pulled, water-cooled, pelletized, and dried to obtain a maleic anhydride grafted modified polyolefin elastomer (TPE-MA-2).

[0039] (2) 2000 g of polypropylene glycol (Mn=1000, Beijing Inokai Technology Co., Ltd.), 120 g of acetic acid (Beijing Inokai Technology Co., Ltd.), and 2.12 g of tetrabutyl titanate were added to a 10 L reactor, replaced with nitrogen three times, heated to 230°C, and then evacuated to an absolute pressure of 200 Pa for 50 min to complete the esterification reaction; the vacuum was stopped, nitrogen was added to 200 kPa, stirring was stopped and the temperature was lowered to 30°C to obtain a monohydroxy-terminated polyether polyol oligomer CJW-002.

[0040] (3) 5 kg of TPE-MA-2 was added to a reactor containing 2120 g of monohydroxy-terminated polyether polyol oligomer CJW-002. After nitrogen replacement three times, the temperature was raised to 230° C. and vacuum was applied to reduce the absolute pressure of the reaction system to below 200 Pa. The reaction was continued for 50 min. The reaction was then pulled, water-cooled, and pelletized to obtain amphiphilic branched copolymer pellets (TPE-PA-2).

[0041]

Preparation Example 3

[0042] (1) 5 kg of POP (Dow VERSIFY 2300, MFR = 0.50 g / 10 min) and 500 g of maleic anhydride monomer (Beijing Inokai Technology Co., Ltd.) and 25 g of azobisisobutyronitrile (Beijing Inokai Technology Co., Ltd.) initiator were uniformly mixed using a high-speed mixer; extrusion was performed using a twin-screw extruder with an aspect ratio of 68, and the temperatures from the feed section to the die were set to 160° C., 210° C., 220° C., 220° C., 210° C., and 200° C. in sequence, and the screw speed was 100 rpm. The extruded material was pulled, water-cooled, pelletized, and dried to obtain a maleic anhydride grafted modified polyolefin elastomer (TPE-MA-3).

[0043] (2) 2000 g of polybutylene glycol (Mn=2000, Beijing Inokai Technology Co., Ltd.), 70 g of propionic acid (Beijing Inokai Technology Co., Ltd.), and 3.11 g of zirconium n-propoxide were added to a 10 L reactor, replaced with nitrogen three times, heated to 220° C., and then evacuated to an absolute pressure of 300 Pa for 40 min to complete the esterification reaction; the vacuum was stopped, nitrogen was added to 300 kPa, stirring was stopped and the temperature was lowered to 30° C. to obtain a monohydroxy-terminated polyether polyol oligomer CJW-003.

[0044] (3) 3.2 kg of TPE-MA-3 was added to a reactor containing 2070 g of monohydroxy-terminated polyether polyol oligomer CJW-003. After nitrogen replacement three times, the temperature was raised to 220° C. and vacuum was applied to reduce the absolute pressure of the reaction system to below 300 Pa. The reaction was continued for 40 min. The reaction was then pulled, water-cooled, and pelletized to obtain amphiphilic branched copolymer pellets (TPE-PA-3).

[0045]

Preparation Example 4

[0046] (1) 5 kg POE (Dow Engage 8150, MFR = 1.0 g / 10 min) and 100 g maleic anhydride monomer (Beijing Inokai Technology Co., Ltd.) and 10 g benzoyl peroxide initiator (Beijing Inokai Technology Co., Ltd.) were uniformly mixed using a high-speed mixer; extrusion was performed using a twin-screw extruder with an aspect ratio of 68, and the temperatures from the feed section to the die were set to 160° C., 210° C., 220° C., 220° C., 210° C., and 200° C. in sequence, and the screw speed was 100 rpm. The extruded material was pulled, water-cooled, pelletized, and dried to obtain a maleic anhydride grafted modified polyolefin elastomer (TPE-MA-1).

[0047] (2) 3000 g of polybutylene glycol (Mn=3000, Beijing Inokai Technology Co., Ltd.), 92 g of n-butyric acid (Beijing Inokai Technology Co., Ltd.), and 1.54 g of dioctyltin oxide were added to a 10 L reactor, replaced with nitrogen three times, heated to 200° C., and then evacuated to an absolute pressure of 500 Pa for 30 min to complete the esterification reaction; the evacuation was stopped, nitrogen was added to 300 kPa, stirring was stopped and the temperature was lowered to 30° C. to obtain a monohydroxy-terminated polyether polyol oligomer CJW-004.

[0048] (3) 12 kg of TPE-MA-1 was added to a reactor containing 3092 g of monohydroxy-terminated polyether polyol oligomer CJW-004. After nitrogen replacement three times, the temperature was raised to 200° C. and the absolute pressure of the reaction system was reduced to below 500 Pa by vacuum. The reaction was continued for 30 min. The reaction was then pulled, water-cooled, and pelletized to obtain amphiphilic branched copolymer pellets (TPE-PA-4).

[0049] [Example 1]

[0050] The nylon 12 elastomer composition was prepared as follows:

[0051] 10kg of nylon 12 elastomer (Arkema Pebax 4033, MFR = 40g / 10min), 10kg of POE (Dow Engage 8150, MFR = 1.0g / 10min), 1000g of amphiphilic branched copolymer (TPE-PA-1), 50g of lubricant EBS (Kao, Japan), 100g of antioxidant 1010 and antioxidant 168, and mixed them for 20min to obtain a mixed material. The mixed material was melt-extruded through a twin-screw extruder with an aspect ratio of 42, water-cooled, pelletized, and dried to obtain a nylon elastomer composition. The screw speed was 150rpm, and the temperature from the feeding section to the die was set to 180-220°C.

[0052] [Example 2]

[0053] The nylon 12 elastomer composition was prepared as follows:

[0054] 10kg of nylon 12 elastomer (Arkema Pebax 4033, MFR = 40g / 10min), 5kg of SEBS (Baling Petrochemical YH-533, MFR = 5.0g / 10min), 500g of amphiphilic branched copolymer (TPE-PA-2), 30g of lubricant EBS (Kao, Japan), 20g of antioxidant 1010 and antioxidant 168, and mixed in a high-speed mixer for 20min to obtain a mixed material. The mixed material was melt-extruded through a twin-screw extruder with an aspect ratio of 42, water-cooled, pelletized, and dried to obtain a nylon elastomer composition. The screw speed was 150rpm, and the temperature from the feeding section to the die was set to 180-220℃.

[0055] [Example 3]

[0056] The nylon 12 elastomer composition was prepared as follows:

[0057] 10kg of nylon 12 elastomer (Arkema Pebax 2533, MFR = 10g / 10min), 7kg of POP (Dow VERSIFY 2300, MFR = 0.50g / 10min), 700g of amphiphilic branched copolymer (TPE-PA-3), 30g of lubricant EBS (Kao, Japan), 50g of antioxidant 1010 and antioxidant 168, etc., were added into a high-speed mixer and mixed for 20min to obtain a mixed material. The mixed material was melt-extruded through a twin-screw extruder with an aspect ratio of 42, water-cooled, pelletized, and dried to obtain a nylon elastomer composition. The screw speed was 150rpm, and the temperature from the feeding section to the die was set to 180-220°C.

[0058] [Example 4]

[0059] The nylon 12 elastomer composition was prepared as follows:

[0060] 10kg of nylon 12 elastomer (Arkema Pebax 7233, MFR = 4g / 10min), 1kg of POE (Dow Engage 8150, MFR = 1.0g / 10min), 100g of amphiphilic branched copolymer (TPE-PA-4), 10g of lubricant EBS (Kao, Japan), 10g of antioxidant 1010 and antioxidant 168, etc., were added to a high-speed mixer and mixed for 20 minutes to obtain a mixed material. The mixed material was melt-extruded through a twin-screw extruder with an aspect ratio of 42, water-cooled, pelletized, and dried to obtain a nylon elastomer composition. The screw speed was 150rpm, and the temperature from the feeding section to the die was set to 180-220°C.

[0061] [Comparative Example 1]

[0062] A nylon 12 elastomer composition was prepared in substantially the same manner as in Example 1, except that the amphiphilic branched copolymer (TPE-PA-1) was replaced with the same mass of maleic anhydride grafted POE (Dow N493).

[0063] [Comparative Example 2]

[0064] A nylon 12 elastomer composition was prepared in substantially the same manner as in Example 1, except that the amphiphilic branched copolymer (TPE-PA-1) was replaced with a compound of the same mass of monohydroxy-terminated polyether polyol oligomer CJW-001 and maleic anhydride grafted modified polyolefin elastomer TPE-MA-1 in a ratio of 1:8.3.

[0065] The nylon 12 elastomer compositions prepared in the examples and comparative examples were tested for properties such as the dispersed phase size, elongation at break, and melt strength of the polyolefin elastomer. The results are shown in Table 1.

[0066] Table 1. Performance test results

[0067]

[0068] From the data comparison in Table 1, it can be seen that in the nylon 12 elastomer composition prepared in Examples 1-4 of the present invention, the size of the polyolefin elastomer dispersed phase is less than 2 μm, indicating that the system has good compatibility, and the improvement of compatibility is conducive to further improving the elongation at break of the composition. In addition, the nylon 12 elastomer composition to which the amphiphilic branched copolymer of the present invention is added exhibits higher melt strength, indicating that the polymer melt has excellent anti-extension and anti-melt sag properties.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A nylon elastomer composition, characterized in that: The invention comprises the following components in parts by weight: 100 parts of nylon elastomer; 20-100 parts of polyolefin elastomer; 1-10 parts of amphiphilic branched copolymer; 0.1-0.5 parts of antioxidant and 0.1-0.5 parts of lubricant.

2. The nylon elastomer composition according to claim 1, characterized in that The nylon elastomer has a melt index of 4-40 g / 10 min under the test conditions of 235° C. and 2.16 kg; Preferably, the polyolefin elastomer has a melt index of 0.5-5 g / 10 min under the test conditions of 235° C. and 2.16 kg; Preferably, the polyolefin elastomer is selected from one or more of POE, POP, SBS and SEBS.

3. The nylon elastomer composition according to claim 1 or 2, characterized in that: The amphiphilic branched copolymer is a copolymer with a polyolefin elastomer as a linear main chain and a polyether polyol oligomer as a branched side chain.

4. The nylon elastomer composition according to any one of claims 1 to 3, characterized in that: The antioxidant is selected from a combination of one or more of antioxidant 1010, antioxidant 1098, antioxidant 168, and antioxidant H10; Preferably, the lubricant is selected from one or more of ethylene bisstearamide, oleamide, silicone oil and paraffin.

5. A method for preparing the nylon elastomer composition according to any one of claims 1 to 4, characterized in that: The following steps are involved: The nylon 12 elastomer, polyolefin elastomer, amphiphilic branched polymer, lubricant and antioxidant are mixed at high speed for 10-20 minutes, melt-extruded, water-cooled, pelletized and dried to obtain a nylon elastomer composition.

6. The method for preparing the nylon elastomer composition according to claim 5, characterized in that: The preparation method of the amphiphilic branched polymer is as follows: S1, mixing a polyolefin elastomer, maleic anhydride and an initiator and then extruding the mixture to obtain a maleic anhydride grafted modified polyolefin elastomer; S2, after mixing the polyether polyol, the monoacid and the catalyst, heating to 200-240°C, then evacuating to an absolute pressure of 100-500Pa, reacting for 0.5-1h; after stopping the evacuation, nitrogen is added to 100-300kPa, stirring is stopped and the temperature is lowered to obtain a monohydroxyl-terminated polyether polyol oligomer; S3, mixing the maleic anhydride grafted modified polyolefin elastomer and the monohydroxyl terminated polyether polyol oligomer obtained in step S1, heating to 200-240° C., evacuating to an absolute pressure of 100-500 Pa, and continuing the reaction for 0.5-1 h to obtain an amphiphilic branched polymer.

7. The method for preparing the nylon elastomer composition according to claim 5 or 6, characterized in that: In step S1, the amount of maleic anhydride added is 2-10% of the mass of the polyolefin elastomer; Preferably, the initiator is selected from at least one of benzoyl peroxide, azobisisobutyronitrile and dicumyl peroxide, and more preferably, the amount of the initiator added is 0.2-0.5% of the mass of the polyolefin elastomer; Preferably, the extrusion temperature in step S1 is 150-250°C.

8. The method for preparing the nylon elastomer composition according to any one of claims 5 to 7, characterized in that: In step S2, the number average molecular weight of the polyether polyol is 500-3000; Preferably, the monoacid is one or more of formic acid, acetic acid, propionic acid, and n-butyric acid. More preferably, the amount of the monoacid added is (0.95-1.05):1 based on the molar ratio of carboxyl group to terminal hydroxyl group of the polyether polyol. Preferably, the catalyst is selected from one or more of tetrabutyl titanate, antimony glycol, dioctyltin oxide, zirconium n-propoxide, and more preferably, the added amount of the catalyst is 0.05-0.2% of the mass of the polyether polyol.

9. The method for preparing the nylon elastomer composition according to any one of claims 5 to 8, characterized in that: In step S3, the mass ratio of the monohydroxyl-terminated polyether polyol oligomer to the maleic anhydride grafted modified polyolefin elastomer is 1:(2-10).

10. Use of the nylon elastomer composition according to any one of claims 1 to 4 or the nylon elastomer composition prepared by the method according to any one of claims 5 to 9 in sole foaming materials and large-diameter pipes.

Citation Information

Patent Citations

  • Environment-friendly electrostatic dissipative polystyrene modified plastic and production method thereof

    CN102516680A

  • Novel amphiphilic graft copolymers

    CN104684948A

  • Melt reinforced polyethylene composition and preparation method thereof

    CN117511030A

  • Nylon 12 composition and preparation method thereof

    CN118165506A

  • Amphiphilic polymer capsules and related methods of interfacial assembly

    US20050096454A1

Cited By

  • Ultralow-temperature nylon flexibilizer, preparation method thereof and toughened nylon

    CN119823394A